(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The term ‘Arabs’ has referred to different peoples atdifferent times. In the modern sense, the term refers to the people who speakArabic as their native language. Ethnically, the term denotes the nomadicpeoples of Arabian peninsula who use Arabic as their mother tongue. Inpre-Islamic times the term was used to designate the inhabitants of Arabianpeninsula. On the advent of Islam, when believers of the new faith were unifiedin to one ‘Ummah’ or community irrespective of their nationality or ethnicaffiliation the term Arab got a wider meaning and began to be used to denoteanyone who professed Islam and used Arabic as his ‘language’. In this study theterm ‘Arab trade’ is used in the wider sense to denote the commercialactivities of a people with diverse ethnic origin, whether it be Persian,Syrian, Egyptian, Turkish, Arabian or any other one, but united by a commonbond of the medieval Arab culture.